2021
DOI: 10.1177/02692155211046463
|View full text |Cite
|
Sign up to set email alerts
|

Setting meaningful goals in rehabilitation: A qualitative study on the experiences of clients and clinicians in working with a practical tool

Abstract: Objective To evaluate the experience of clients and clinicians in working with a tool to help set goals that are personally meaningful to rehabilitation clients. Design We have applied the tool in the outpatient rehabilitation setting. Clients’ and clinicians’ experiences in working with the tool were evaluated in individual, semi-structured interviews and focus group interviews, respectively. Thematic analysis was used to analyze the data. Setting A university medical center and a rehabilitation center. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the case of HAE patients, who often present signi cant limitations in their level of autonomy, as well as in private and working-related relationships, rehabilitation, intended as the achievement of the highest possible level of independence and participation in daily life and working activities, becomes a fundamental part of the care process. To be effective in terms of health results and costs, rehabilitation also bene ts from the proposed approach focused on personalized interventions centred on the individuals' needs and values [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of HAE patients, who often present signi cant limitations in their level of autonomy, as well as in private and working-related relationships, rehabilitation, intended as the achievement of the highest possible level of independence and participation in daily life and working activities, becomes a fundamental part of the care process. To be effective in terms of health results and costs, rehabilitation also bene ts from the proposed approach focused on personalized interventions centred on the individuals' needs and values [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…35,36 The person is central to the general theory of behaviour, 37 which stresses that people have a purpose as part of their identity, 38 working towards meaningful goals, which can be identified in rehabilitation. 39,40 The person is central to healthcare. William Osler (1849-1919) summarised this in an aphorism, 'Ask not what disease the person has, but rather what person the disease has'.…”
Section: Biopsychosocial Adaptationmentioning
confidence: 99%
“…The person is central to the general theory of behaviour, 37 which stresses that people have a purpose as part of their identity, 38 working towards meaningful goals, which can be identified in rehabilitation. 39 , 40 …”
Section: Introductionmentioning
confidence: 99%
“…National Clinical Guidelines promote goal setting as an essential aspect of stroke rehabilitation. Many studies have shown improvement in patients' confidence and motivation to work on rehabilitation with prior goal setting to improve motor and cognitive skills [ 23 , 24 ]. There are some different goal perspectives between patients and hospital staff that impede the development of the patient.…”
Section: Reviewmentioning
confidence: 99%